Study of Profitability and Efficiency Between SOEs and POEs Before and After Financial Crisis in 2008 - Peng, Xilin (2013)
With economic development, China stock market is increasingly significant in the world. State owned enterprises were crucial part of China economy but they were criticized for unprofitability and inefficiency. Therefore, the relationship between state ownership and firm performance is frequently studied. This dissertation aims to investigate the differences between profitability and efficiency between state-owned enterprises (SOEs) and private owned enterprises (POEs). Extant literatures documented various even conflicting results in this topic. Some believe that agency problem is the root of governance inefficiency and poor performance in SOEs while others report that there is no significant improvement after privatization. The existing controversial insights suggest that there should be more investigation based on recently background. A global financial crisis occurred in 2008, which had severe impact on many countries include China. Therefore, the second aim of this paper is to test the survival ability in severe environment, such as financial crisis, which few studies had recorded in existing documents. The empirical study in this paper base on the data collected from 2003 to 2012, a period of ten-year. Financial statements are important data source and two comparisons are the key components of this paper. The first comparison is between SOEs and POEs with regard to profitability and efficiency. The second comparison focuses on the performance of five-year period before and after global crisis in 2008. It is concluded in this paper that in normal cases, POEs are superior to SOEs in terms of earning power and corporate efficiency. However, SOEs demonstrate more powerful validity and survival ability in severe environment.